HIGH INTENSITY INTERVAL TRAINING (HIIT) SAMA BAIKNYA DENGAN CIRCUIT WEIGHT TRAINING DALAM MENURUNKAN PERSENTASE LEMAK TUBUH DAN MENINGKATKAN KAPASITAS VITAL PARU - Yudistira, Efraldo; Satriyasa, Bagus Komang; Indra Lesmana, Syahmirza; Inten Dwi Primayanti, Dewa Ayu; Sandi, I Nengah; Imron, Ali (Sport and Fitness Journal, 2018)
High-intensity exercise exercises in the exercise process use enormous amounts of muscle glycocal energy to strengthen adipose tissue into energy acids, energy requirements balanced with oxygen demand that will improve pulmonary performance and physiology. Weight-adjusting exercises are adjusted to the adaptation and physiology of muscles, increased muscle development and physiological muscles and muscles increases into more so that the energy process increases both muscle glycogen and increased fat oxidation. In this study the sample will be divided into 2 groups, group I will be given High intensity interval training, group II will be given Circuit weight training, both groups aim to reduce the percentage of body fat and increase the vital capacity of the lung. This study measures the pre and post test results so that it will be measured before treatment and after treatment after the exercise program for 6 weeks. Samples will be measured using Bioelectrical Impedance Analisys to measure the percentage of body fat and Spirometry to measure vital pulmonary capacity.The results of the first group hypothesis test showed the value before the fat percentage of 21.75 and after training to be 19.46, then before the vital capacity of the lungs 2.32 and after training to 4.02. While in group 2 the fat percentage value was 21.55 and the training was determined to be 19.79. For the value of vital capacity of lung 2.46 and after training to 3.64, with the probability value in both groups was 0.000 which means (p <0.05) and the measurement was no significant difference from both exercises. In the test of hypothesis III the comparison of results in group I , II, t-test independent sample with the result of the average group I fat difference 2.29 ± 0.46, KVparu 1.75 ± 0.55, Group II fat% 1.70 ± 0.43, KVparu 1.17 ± 0.45 with fat% probability value (p = 0,725) and KVparu (p = 0,073) which means (p> 0,05) and can. There was no significant difference between the three interventions.The conclusion of this research is high intensity interval training as well as ciecuit weight training in decreasing body fat percentage and increasing vital capacity of lung